2019
DOI: 10.21203/rs.2.310/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of FOXP3 gene rs3761548 and rs2232365 polymorphism and multiple sclerosis susceptibility

Abstract: Background: Multiple sclerosis (MS) is a common autoimmune disease of the central nervous system (CNS), and is associated with genetic factors. FOXP3 gene polymorphism has been reported as the risk factor for MS, however, previous studies have showed conflicting results. The purpose of this study is to investigate the impact of FOXP3 gene polymorphism on the MS susceptibility through a meta-analysis. Methods: Pubmed, Embase, library of Cochrane, and Web of Science were used to search the eligible articles up t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our study also shows that there is a significant association between reduced FOXP3 gene expression and a positive family history of autoimmune disease ( p = 0.03). In 2016, a study of different variants of FOXP3 found a significant difference in the distribution of the rs3761548 and rs2232365 alleles in MS patients compared to controls, suggesting that this polymorphism leads to suppression of FOXP3 30 . The study found that 24% of MS patients who had recently been exposed to a viral disease such as COVID‐19 or influenza had a greater decrease in FOXP3 expression, which may be due to a significant reduction in the number of Treg cells following chronic neuroinflammation in the setting of viral infection 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also shows that there is a significant association between reduced FOXP3 gene expression and a positive family history of autoimmune disease ( p = 0.03). In 2016, a study of different variants of FOXP3 found a significant difference in the distribution of the rs3761548 and rs2232365 alleles in MS patients compared to controls, suggesting that this polymorphism leads to suppression of FOXP3 30 . The study found that 24% of MS patients who had recently been exposed to a viral disease such as COVID‐19 or influenza had a greater decrease in FOXP3 expression, which may be due to a significant reduction in the number of Treg cells following chronic neuroinflammation in the setting of viral infection 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the association study is a viable approach toward recognizing the risk genetic loci of genes as a marker such as SNP. Among these was reported the relationship of many IL-7 receptor SNPs with MS in various ethnic groups (Sahami-Fard et al, 2020, Zhang et al, 2019. The position of IL7R is chromosome 5 short arm 13 (5p13).…”
Section: Introductionmentioning
confidence: 99%
“…Immunological incompatibility between mother and fetus is frequently observed in preeclampsia and genetic factors related to the immunological pathway in preeclampsia have been discovered [12]. In Asian, rs3761548 polymorphism was significantly associated with multiple sclerosis, an immune-related central nervous disease [13]. In the Chinese Han population, rs2232365 and rs3761548 polymorphisms confer an important susceptibility to unexplained recurrent spontaneous abortion by altering Foxp3 function and/ or its expression [14].…”
Section: Introductionmentioning
confidence: 99%